Analisis Pengaruh Fraksi Volume Serat Rambut Manusia dan Dedak Padi terhadap Sifat Mekanik dan Morfologi Komposit Poliester : Analysis of the Effect of Volume Fraction of Human Hair Fiber and Rice Bran on the Mechanical Properties and Morphology of Polyester - yoga ahdiat fakhrudi; Pradhana Kurniawan; M. Shafwallah Al. Aziz; Imam Basuki; Agung Kurniawan; Hilmi Muhtadi (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
Natural fiber-based composites have several advantages, including relatively light weight, good strength, easy processing, and environmentally friendly. This study aims to analyze the effect of variations in the volume fraction of human hair fibers on the mechanical properties of polyester composites, including tensile strength and impact strength, as well as macro and micro morphology. The method used is an experiment with the manufacture of composite specimens using hand lay-up with variations in the volume fraction of hair fibers and dadak fibers: 15 wt%: 15 wt%, 20 wt%: 10 wt%, 25 wt%: 5 wt%. The test results show that variations in the volume fraction have a significant effect on the mechanical properties of human hair fiber composites. The highest tensile strength value of 27.7 MPa was obtained at a volume fraction variation of 25:5, while the lowest value was 23.6 MPa. In the impact test, the highest value of 0.00597 J/mm² was also obtained at a variation of 25:5, while the lowest value was 0.00482 J/mm².